Metastatic Site in Pancreatic Adenocarcinoma Correlates with Prognosis - Cereda, Stefano; Belli, Carmen; Rognone, Alessia; Passoni, Paolo; Slim, Najla; Carvello, Michele; Ariotti, Riccardo; Balzano, Gianpaolo; Reni, Michele (JOP. Journal of the Pancreas, 2012)
Context Pancreatic adenocarcinoma (PA) is mostly metastatic at time of diagnosis with a poor survival. Objective We decided to explore whether metastatic site correlates with prognosis. Methods Patients with pathologic diagnosis of metastatic PA, treated at our Institution with upfront combination chemotherapy between April 1997 and August 2010 were eligible for this analysis. Baseline tumor assessment consisted of contrast enhanced computed tomography scan of the abdomen and the thorax. Results Two-hundreds and sixty-five patients with metastatic PA, median age 60 years; median PS 90; median CA 19-9 1,048 were eligible; 19 (7.2%) had prior pancreatic surgery. Metastases were located: in a single organ (n=150; 56.6%); liver (n=227; 85.3%); peritoneum (n=32; 12.1%); lung (n=53; 19.9%). Lung was the only metastatic site in 15 cases (5.6%). Median and 1-year overall survival (OS) was 9.0 months and 32.2%. Prior surgery correlated with better OS (11.7 and 51.0% versus 8.9 and 30.8%; P=0.006); liver metastases with worse OS (median and 1-year OS: 8.8 months and 29.7% versus 11.1 and 47.4%; P=0.005); while no difference in OS was observed based on number of metastatic sites (P=0.37); peritoneal (P=0.50) or lung metastases (P=0.10). Patients with lung as isolated metastatic site lived longer (17.3 months and 66.7%) with respect to the whole population (9.0 months and 30.1%; P=0.01) and to patients with lung metastases associated to other metastatic sites (8.8 months and 34.2%; P=0.07). Conclusions Prior surgery and metastatic site correlate with prognosis and should be used as a stratification criterion in prospective trials. Patients with lung as isolated metastatic site has a particularly good prognosis.